Notions about landscape and their implications in planning (Ciudades, 2018)
This text makes reference to the polysemy of the concept of landscape, as well as to the use that the different disciplines make of it, and its interdependence with another terms such as environment, scene, identity, ambiance, character, etc.; all this has driven to a lack of precission in the terms or a conceptual mischief that is clearly manifested in the legislation, that seems to settle the meanings ot the concept of landscape between the values of the environment and those of the cultural heritage. Undoubtedly, as a cultural concept, the landscape has many faces but, in order to perform a proper landscape planning in the context of the spatial planning, it proves to be urgent to come to an agreement about the basic aspects that define it.
Keywords: terminolgy about landscape; cultural landscape; spatial planning; Spanish legislation